How do you find the solution to the quadratic equation 0 = x^2 + 5x + 60=x2+5x+6?

3 Answers
Jun 20, 2018

x=-2 or -3

Explanation:

x^2+5x+6=0x2+5x+6=0

x^2+2x+3x+6=0x2+2x+3x+6=0

x*(x+2)+3(x+2)=0x(x+2)+3(x+2)=0

(x+2)*(x+3)=0(x+2)(x+3)=0

x=-2 or -3x=2or3

Jun 20, 2018

x=-3, x=-2x=3,x=2

Explanation:

Lets factorise:

(x+3)(x+2)=0(x+3)(x+2)=0

Check this is correct...

x^2+3x+2x+6x2+3x+2x+6

rArr x^2+5x+6=0x2+5x+6=0

Now solve:

(x+3)=0(x+3)=0

therefore x=-3

(x+2)=0

therefore x=-2

Jun 21, 2018

x=-2 and x=-3

Explanation:

Are there any two numbers that sum to the middle term (5), and have a product of the last term (6)?

After some trial and error, we arrive at

2 and 3. Thus, we can factor the right side of our quadratic as

0=(x+2)(x+3)

Setting both of our factors equal to zero, we get

x=-2 and x=-3

Hope this helps!